Stress in Young Adult Age and its influence in Social Life/The Role of Self-Esteem - Peleti Nikoleta (2015)
Abstract, Introduction, Method, Design, Participants, Materials, Procedure, Results, Discussion, Reference, Appendices, Forms, Questionnaires, SPSS Results, PDP and CV.